A Meta-analytic Review: Psychological Treatment of Subthreshold Depression in Children and Adolescents - Cuijpers, Pim; Pineda, Blanca S; Ng, Mei Yi; Weisz, John R; Muñoz, Ricardo F; Gentili, Claudio; Quero, Soledad; Karyotaki, Eirini (Journal of the American Academy of Child and Adolescent Psychiatry, 2021)
Subthreshold depression has been found to be associated with considerable impairment and an increased risk of developing major depression. Although several randomized trials have examined the effects of psychological interventions for subthreshold depression in children and adolescents, no meta-analysis has integrated the results of these trials. We searched 4 bibliographic databases and included randomized trials comparing psychological interventions with control conditions in children and adolescents scoring above a cut-off of a depression questionnaire but not meeting diagnostic criteria for major depression (or persistent depressive disorder) according to a diagnostic interview. Effect sizes and incidence rates of major depression were pooled with random effects meta-analyses. A total of 12 trials with 1,576 children and adolescents met inclusion criteria. The overall effect size indicating the difference between treatment and control at post-test was g = 0.38 (95% CI = 0.14-0.63), which corresponds to a number-needed-to-treat (NNT) of 8.4. Heterogeneity was moderate to high (I = 61; 95% CI = 28-79), and there was significant risk of publication bias (p < .04). The 2 studies in children less than 12 years of age showed nonsignificant effects (g = 0.01; 95% CI = -1.16 to 1.18). We found no significant effect on the incidence of major depression at follow-up (relative risk = 0.52; 95% CI = 0.25-1.08), although this may be related to low statistical power. Interventions for subthreshold depression may have positive acute effects in adolescents. There is currently insufficient evidence, however, that these interventions are effective in children less than 12 years of age, or that they prevent the onset of major depression at follow-up.